IBX-Mediated Organic Transformations in Heterocyclic Chemistry-A Decade Update - Venkata Durga Nageswar, Yadavalli; Ramesh, Katla; Rakhi, Katla (Frontiers in Chemistry, 2022)
o-Iodoxybenzoic acid (IBX) is a very mild and efficient hypervalent iodine synthetic reagent useful to carry out several selective oxidations. The present review highlights research reports on IBX assisted transformations in heterocyclic derivatives, particularly from 2010 onwards.